Genome-wide transcription profiling in neutrophils in acute respiratory distress syndrome. (26th February 2015) - Juss, JatinderK; Herre, Jurgen; Begg, Malcolm; Bradley, Glyn; Lennon, Mark; Amour, Augustin; House, David; Hessel, Edith M; Summers, Charlotte; Condliffe, Alison M; Chilvers, Edwin R
Abstract: Background: Acute respiratory distress syndrome (ARDS) is characterised by diffuse neutrophil-mediated alveolar inflammation. Recently, we demonstrated that blood polymorphonuclear leucocytes (PMNs) in ARDS are basally activated, and exhibit aberrant oxidative burst and survival responses. The molecular mechanisms governing ARDS PMN function and longevity are incompletely understood. We aimed to use genome-wide transcriptional profiling of ARDS blood PMNs to explore underlying disease mechanisms and identify therapeutic targets aimed at manipulating PMN function and longevity. Methods: GeneChip Affymetrix oligonucleotide arrays were used to assess global transcriptional profiles in highly pure PMNs from ventilated patients fulfilling the Berlin ARDS definition (n=10), in freshly isolated PMNs from age-matched and sex-matched healthy volunteers (n=10), and in healthy volunteer PMNs exposed in vitro to recombinant human granulocyte-macrophage colony stimulating factor (rhGM-CSF) (1 ng/mL for 6 h). Ingenuity Pathway Analysis software was used to map probes identified as important onto specific pathways. Findings: Transcriptomic analysis showed that 1319 genes were altered in ARDS PMNs relative to healthy volunteer PMNs. Compared with well established reference databases, the gene expression profile in ARDS PMNs showed near-complete correlation to datasets derived from patients with sepsis and burns. Transcripts enriched in ARDS PMNs were differentially expressed in known functional network pathways associated with cancer, cellular compromise, apoptotic mechanisms, and chemotaxis. Of the observed gene changes, only 292 (22%) were seen in healthy volunteer PMNs after exposure to rhGM-CSF, of which 216 showed the same directional change as ARDS PMNs. Interpretation: Existing genome-wide studies in ARDS use total blood leucocytes; our study is the first, to our knowledge, to use unbiased global genomic profiling of highly pure ARDS blood PMNs in parallel with age-matched and gender-matched healthy volunteer PMNs treated with rhGM-CSF. Collectively our results show that ARDS PMNs display important de-novo transcriptional activity. The global transcriptomic changes were consistent with the observed aberrant ARDS PMN survival and functional phenotype that we have previously reported, and show near-complete correlation to existing sepsis and burns datasets, but only limited transcriptomic overlap with healthy volunteer PMNs treated with rhGM-CSF. Funding: National Institute for Health Research, GlaxoSmithKline.